Representação de modelos pulmonares usando malhas triangulares - Silva, Samuel (2004)
3D models based on polygonal meshes are being increasingly used in many application areas, in particular formedical visualization. After a short presentation of the traditional mesh processing pipeline, the sequence ofoperations carried out to construct lung models, from their segmented contours, using triangular meshes and the OpenMesh library, is described.